Artificial intelligence and computer vision - Lu, Huimin; Li, Yujie (Springer, 2016)
This edited book presents essential findings in the research fields of artificial intelligence and computer vision, with a primary focus on new research ideas and results for mathematical problems involved in computer vision systems. The book provides an international forum for researchers to summarize the most recent developments and ideas in the field, with a special emphasis on the technical and observational results obtained in the past few years.
Includes author index.
Keywords: Artificial intelligence.; Computer vision.; elektronické knihy; electronic books